Feasibility of minimum intervention oral healthcare delivery for individuals with dental phobia - Ellie Heidari; Avijit Banerjee; Jonathon Tim Newton (BMC, 2023)
Abstract Background People with dental phobia often present with more active dental caries and fewer teeth. Minimally Intervention oral Healthcare offers a possible solution to address the high care needs of this group. The aim was to determine this patient group's eligibility and willingness to participate and the effect of MIOC, compared to treatment as usual (TAU), on their oral health outcomes for planning a future randomised controlled trial (RCT). Minimum intervention oral healthcare (MIOC) comprises of four interlinked domains. In the first domain, we identified and diagnosed the disease status and participants' anxiety status (≥ 19 MDAS). In the second domain, an individualised prevention-based personalised care plan was designed. During this process, patients with dental phobia were exposed to the dental environment in a stepped manner ('graded exposure') and had their urgent care provided with conscious sedation. In the 3rd domain, we took a minimally invasive operative approach to restore teeth while preserving tooth substance and limiting the use of fear-provoking stimuli (e.g., rotary instruments) when possible. At the review and the recall appointment(s) (4th domain), the patients' oral health care behaviours, disease risk/susceptibility and fear levels were re-assessed. Methods This two-arm randomised feasibility trial (N = 44) allocated participants to the experimental arm (MIOC) or the control arm (treatment as usual [TAU]). The primary outcomes were the eligibility and willingness to participate and feasibility to conduct a trial of MIOC for people with dental phobia. The secondary outcomes were oral health status, oral health related quality of life and care completion. A written and verbal consent for participation and dental care provision were obtained. Results Forty-four people diagnosed with dental phobia were allocated randomly to the two study arms. At the six-month recall after completed care, the outcome of each study arm was assessed. It was feasible to conduct a clinical trial (eligibility rate [56%], completion rate [81%], declined to participate [12%]). The intervention group showed improvements in all health care outcomes, and oral health related quality of life. Conclusion A clinical trial of MIOC vs TAU in people with dental phobia is feasible. Preliminary findings suggest that patients in the MIOC arm are more likely to successfully complete their course of treatment. The study was 'retrospectively registered' on 02/05/2018 (ISRCT15294714) with the International Standard Randomised Controlled Trial (ISRCT).